Perancangan Sistem Informasi Monitoring Status Kontrak Jasa pada Departemen Pengadaan Jasa PT. Pupuk Sriwidjaja Palembang - Pani Munika; M. Syendi Apriko (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The management and monitoring of service contract status in the Service Procurement Department of PT. Pupuk Sriwidjaja Palembang (PT Pusri) currently rely on manual methods using Microsoft Excel. This manual system has numerous limitations that lead to problems, such as difficulty in tracking contract status (active, nearing expiration, or expired), delays in identifying contracts about to expire, and the potential for data input errors. These limitations are compounded by the lack of fast and accurate monitoring reports, which hinders the managerial decision-making process. This research aims to design an information system for monitoring service contract status that can help employees of the Service Procurement Department monitor contract status in a more structured, accurate, and efficient manner. The research method used is applied research with an information system development approach utilizing the Waterfall method. The Waterfall method was chosen because it provides a systematic and structured workflow. The stages of this research include Requirements Analysis, conducted through interviews and direct observation of business processes; System Design, which covers the design of the user interface and database; Implementation, in the form of creating a web-based system prototype; and Testing. The result of this research is a monitoring information system design that is expected to facilitate real-time contract monitoring, clearly display contract status, and generate reports that support corporate decision-making.